Brush Of Wings - Kingsbury, Karen; Heyborne, Kirby; LaVoy, January; Tonn, Travis; Simon & Schuster Audio (Firm) (New York : Simon & Schuster Audio, 2016)
The third novel in the series about divine intervention and the trials and triumphs of life for a group of friends whose lives could affect the future of the country.
Keywords: Guardian angels. -- Fiction; Women social workers -- Fiction; Orphanages -- Fiction -- Uganda; Baseball players -- Fiction; Heart -- Fiction -- Transplantation; Life change events -- Fiction; Miracles -- Fiction; Audiobooks; Audiobooks; Christian fiction; Romance fiction